Unraveling the prognostic significance and molecular characteristics of tumor-infiltrating B lymphocytes in clear cell renal cell carcinoma through a comprehensive bioinformatics analysis - Yue, Youwei; Cai, Xinyi; Lu, Changhao; Sechi, Leonardo Antonio; Solla, Paolo; Li, Shensuo (Frontiers in Immunology, 2023)
Clear cell renal cell carcinoma (ccRCC) is a prevalent subtype of kidney cancer that exhibits a complex tumor microenvironment, which significantly influences tumor progression and immunotherapy response. In recent years, emerging evidence has underscored the involvement of tumor-infiltrating B lymphocytes (TIL-Bs), a crucial component of adaptive immunity, and their special roles in ccRCC as compared to other tumors. The present study endeavors to systematically explore the prognostic and molecular features of TIL-Bs in ccRCC. Utilizing various public bulk RNA-seq cohorts and xCell deconvolution algorithm, we firstly found that TIL-Bs in TCGA-KIRC exclusively display a relationship with poor prognosis. Further analysis through WGCNA and Consensus cluster methods revealed the existence of several co-expression modules associated with TIL-Bs and detected a distinct ccRCC cluster. Moreover, we assessed the transcriptomic alteration of B cells in ccRCC tumor environment derived from an scRNA-seq dataset. Based on hub genes of two core modules, a 10-gene prognostic signature (TNFSF13B, SHARPIN, B3GAT3, IL2RG, TBC1D10C, STAC3, MICB, LAG3, SMIM29, CTLA4) was developed using Cox regression in the train set, which was validated in both internal and external test sets. Subsequently, the signature biomarkers were further investigated with regards to their differential expression and correlation with immune characteristics in tumor condition, along with risk-score related mutations and pathways. Lastly, two additional explorations for the signature were proposed for clinically predictive and therapeutic use, including the establishment of a personalized nomogram and the discovery of potential drugs for ccRCC. Overall, our study offers comprehensive sights to the features of TIL-Bs This is a provisional file, not the final typeset article in ccRCC via multiple bioinformatic analysis. Understanding the roles of TIL-Bs may aid in the creation of innovative immunotherapeutic approaches for ccRCC. Additional research is necessary to authenticate and clarify its clinical implications for patient prognosis and treatment efficacy.